Pengaruh Faktor Lingkungan Terhadap Pola Distribusi Spasial Dan Temporal Musuh Alami Di Lahan Pertanian - ASYIK NUR ALIFFAH; NUR ALIM NATSIR; MUHAMMAD RIJAL; SALMA SAPUTRI (INSTITUT AGAMA ISLAM NEGERI AMBON, 2019)
Natural enemies are one component of Integrated Pest Management that utilizes non-chemical methods and reduces pesticides. Physical factors of the environment both temperature, humidity and varying light intensity greatly affect the abundance of natural enemies in an agricultural ecosystem. The purpose of this study was to determine the number and types of natural enemies of visitors to the observation plots, species diversity (H ') and the influence of environmental factors on the spatial and temporal distribution patterns of natural enemies on agricultural land. Sampling was conducted in May until July 2019. Observations were made grouped into 4 periods are at 07.00-08.00 WIT, 09.00-10.00 WIT, 12.00-13.00 WIT and at 15.00-16.00 WIT. The observation method used is to use